2022
DOI: 10.3389/fsurg.2022.915818
|View full text |Cite
|
Sign up to set email alerts
|

Basal Cisternostomy for Severe TBI: Surgical Technique and Cadaveric Dissection

Abstract: IntroductionCisternostomy is emerging as a novel surgical technique in the setting of severe brain trauma. Different surgical techniques have been proposed with a variable degree of epidural bone work. We present here the surgical technique as it is currently performed in our Institution.MethodsAnatomical dissection of one adult cadaveric head, injected and non-formalin fixed was perfomed. A large right fronto-temporo-parietal craniotomy was accomplished. Extradural sphenoidal drilling till opening of the supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…In another retrospective study, Giammattei et al found that patients treated with DC and cisternostomy had better clinical outcomes [ 6 ]. The same group described cisternostomy’s cadaveric dissection and surgical technique in a separate paper [ 5 ]. A previous case report by our group demonstrated the effect of cisternostomy in decreasing ICP and its potential role as a surgical treatment for pseudotumor cerebri [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In another retrospective study, Giammattei et al found that patients treated with DC and cisternostomy had better clinical outcomes [ 6 ]. The same group described cisternostomy’s cadaveric dissection and surgical technique in a separate paper [ 5 ]. A previous case report by our group demonstrated the effect of cisternostomy in decreasing ICP and its potential role as a surgical treatment for pseudotumor cerebri [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances indicate that ventricular CSF does not communicate with parenchymal IF [ 5 , 6 , 8 ]. As a result, CSF diversion from the ventricular system does not have a strong effect in increasing IF drainage and subsequently decreasing edema and ICP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Allowing CSF drainage through the cisterns by surgically opening them to atmospheric pressure may stimulate CSF and interstitial fluid drainage through the Virchow-Robin spaces, subsequently decreasing ICP [ 10 ]. Many previous clinical studies have shown that cisternotomy with decompressive craniotomy (DC) is associated with better outcomes when compared to DC alone in patients with traumatic brain injury [ 10 , 11 ]. Theoretically, other causes of increased ICP, such as IIH, can benefit from cisternotomy.…”
Section: Discussionmentioning
confidence: 99%